ASIMETRI INFORMASI DAN UNDERPRICING : STUDI EMPIRIS DI BURSA EFEK INDONESIA - , TETI ANGGITA SAFITRI, Prof. Dr. Eduardus Tandelilin, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The initial public offering is an activity made by the company in event of the public offering of stock sales. The shares listed on the primary market are generally enthused by the investors because they give a high initial return. This return indicates the occurence of underpricing in the primary market. Underpricing is a condition in which the share price at the time of offering is relatively too cheap compared to price in the secondary market. The aim of this research is to examine the effect of asymmetric information on underpricing. This research used a sample of 63 companies that make initial public offering on the Indonesia Stock Exchange in the period of 2005-2010. The data analysis is using multiple linear regression, which is testing the proxy of asymmetric information which consists of the firm size, the firm age, the proportion of shares offered to the public, underwriter reputation and auditor reputation on underpricing. This research indicates that underwriter reputation and auditor reputation have a significant effect on underpricing. Meanwhile, the firm size, the firm age and the proportion of shares offered to the public have no significant effect on underpricing.